EFFECT OF ORGANIC AND INORGANIC FERTILIZERS ON GROWTH AND FLOWER QUALITY OF POTTED BEGONIA AND PETUNIA - Thang, Vu; Gioi, Dong; Tang, Li; Ngoc, Nguyen (Tạp chí Khoa học Nông nghiệp Việt Nam, 2024)
The objective of this study was to evaluate the effect of organic and inorganic fertilizers on growth and quality of potted flowers. Three types of fertilizer (composite organic fertilizer (COF), composite inorganic fertilizer (CIF), and foliar spray of multi-nutrients (FSMN) were used for two flower species, Begonia (Begonia semperflorens) and Petunia (Petunia hybrid Vilm). The results showed that application of fertilizers enhanced the growth, physiology, and quality of both flower species. The growth characteristics and quality of both flower species in COF treatment were higher than those in other fertilizer treatments. Specifically, treatment of COF stimulated growth of lateral branch, number of leaves, leaf chlorophyll value and photosynthetic rate of both species. In addition, the highest flower diameters, number of flowers/plants, and flower longevity were observed in COF treatment. Days to first flowering of both species in COF treatment were also shorter than those in other treatments.